MEMBANGUN TERAS IMPIAN MELALUI KULIAH KERJA NYATA DI DESA SAPTA MULIA - Nur Habibah; Aldino Aldino; Reni Guswita; Gusril Ihza Saputra (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2023)
KKN is a form of Tridharma that is actually carried out. It is called devotion. These activities give the integration between college and society. Sapta Mulia village is located at Tebo. It is a large village that has eight hamlets. Based on the statistics, the last education of the society is elementary school and junior high school. It affects people's understanding of how important education is. Sapta Mulia has a lot of education facilities but they do not have study assistance that supports students’ learning. Teras Impian is built by some activities. They are socialization of the importance of education for children and study assistance. The result of Teras Impian is the society of Sapta Mulia village is more understanding about how important of education is for children and the children have more of a will to study more from elementary school to junior high school.